Does 20 mg long-acting methylphenidate alter blood pressure and heart rate in children with ADHD? - Tjhin Wiguna; Sasanto Wibisono; Sudigdo Sastroasmoro; Fransiscus D. Suyatna (Indonesian Pediatric Society, 2011)
Objective To identify the cardiovascular effects of long-acting methylphenidate administered for twelve weeks in Indonesian children with ADHD.Methods This was an 18-week, time series study on children with ADHD who were given 20 mg of long-acting methylphenidate for twelve weeks. During the study period we made ten serial observations of the subjects, including before, during and 6 weeks following drug administration. We included drug naive children with ADHD between the ages of 7 – 10 years. Children with mental retardation and chronic physical or mental disorders were excluded. Blood pressure was measured by sphygmomanometer with a child’s cuff at the brachial artery. We also collected data on heart rate, side effects, complaints and other medications used during the study. Repeated analysis was performed on the data with a P level of 0.05.Results Twenty-one subjects were recruited for this study. Mean blood pressure fluctuated insignificantly during the research period, for both mean systolic and mean diastolic blood pressures (P=0.115 and P=0.059). Mean heart rate also fluctuated insignificantly (P=0.091). All fluctuations were within the normal ranges. During the study, there were complaints of dizziness, nausea, and gastrointestinal upset, but they were reportedly mild and disappeared before the second week of observation.Conclusion Administration of 20 mg long-acting methylphenidate for twelve weeks in children with ADHD altered mean blood pressures and heart rates, but within the normal range for children of their age. However, cardiovascular risk observation is still needed when administering methylphenidate to children with ADHD, especially for those using the medication long-term.[Paediatr Indones. 2011;51:282-7].